ANALISIS YURIDIS PERTANGGUNG JAWABAN PIDANA TERHADAP PELAKU PENCEMARAN NAMA BAIK MELALUI MEDIA SOSIAL (PUTUSAN NOMOR 710/PID.SUS/2021/PN JKT.TIM: Juridical Analysis of Accountability Criminal Defamation Perperators Either Trough Social Media (Verdict Number 710/PID. SUS/2021/PN Jkt. Tim) - Dewas Saputra; Andi Widiatno (Universitas Trisakti, 2024)
Defamation is an event where social interaction in the community environment harms one party, both materially and immaterially. With the development of the digital world, which moves social interaction from the real world to the digital world, it causes a newtype of crime, namely defamation on social media, and this type of crime is included in the category of computer-related crime. The legal basis for enforcing this criminal act of pollution is regulated in the Criminal Code and Law Number 19 of 2016 concerningInformation and Electronic Transactions. With the existence of dif erent forms of accountability for perpetrators of criminal acts, this is the basis for the creation of this paper using the library research method. This type of research is normative, with the nature of analytical descriptive research, and draws conclusions using deductive logic. There are several similarities in the acquittal and guilty verdicts, namely the existence of acts that allegedly attacked the victim's honor by perpetrators based on slander and the application of errors in the judge's considerations that looked more at psychological errors than normative errors